Suitability of the forearm for non‐invasive blood pressure measurement in children. Issue 11 (13th October 2017) - Greaney, David; Nakhjavani, Solmaz; Desmond, Fiona; Tormey, Mark; Dawkins, Ian; O'Hare, Brendan
Summary: Background: Measurement of forearm blood pressure (BP) in pediatric patients during general anesthesia is periodically employed despite a lack of evidence for this practice. Upper arm BP measurement may be impossible to perform for either patient or surgical reasons, and the forearm has theoretical benefits over the lower leg when an alternate site is required. We hypothesize that forearm BP measurement provides an accurate and reliable alternative to the upper arm. Published adult data do not support this hypothesis, and the little pediatric data published contain methodological shortcomings. Methods: A dedicated, externally calibrated noninvasive oscillometer was used to compare BP measurements in the upper arm and ipsilateral forearm of pediatric patients undergoing general anesthesia prior to application of a surgical stimulus. Both upper arm BP and ipsilateral forearm BP were sequentially measured 20 seconds apart on 3 separate occasions with an appropriately sized cuff. The systolic, diastolic, and mean blood pressures were recorded under steady‐state conditions. Results: Thirty‐five elective surgical patients aged 1 to 10 years were studied. The bias (±limits of agreement) for forearm minus upper arm blood pressures were as follows: mean BP −1.3 mm Hg (±7.2), diastolic BP −3.3 (±5.3), and systolic BP +3.2 mm Hg (±8.3). Differences greater than ±5 mm Hg occurred in 59% (systolic BP), 42% (diastolic BP), and 46% (mean BP) of all observations and greater than ±10 mm Hg in 17% (systolic BP), 8.6% (diastolic BP), and 15% (mean BP). Conclusion: The differences within mean ±1.96 standard deviations reside considerably outside the clinically accepted tolerance of ±5 mm Hg. Thus, the forearm may not be used interchangeably with upper limb BP readings in anesthetized healthy children. Future use of the forearm for BP measurement requires a validated anthropomorphically appropriate forearm cuff.